The Factors Causing Discrimination Against Indonesian Women in the Workplace, Mapping of Problems from 2012 to 2022 - Verdico Arief; Magdalena Depriyani; Asri Hidayati (Eduvest - Journal of Universal Studies, 2025)
Indonesia, one of the world's most populous nations with a significant female population, continues to face workplace gender discrimination despite legislative frameworks and improving gender equality rankings. Although Indonesia rose to 92nd globally in 2022 (from 99th in 2021), gaps between policy and practice remain, especially regarding women’s participation and advancement in employment. This study fills a critical research gap by systematically mapping factors behind workplace discrimination against Indonesian women. A search across four major databases (ScienceDirect, Emerald Insight, Sage, and Taylor & Francis) for "discrimination against Indonesian women in the workplace" yielded 5,605 results. After filtering, 38 peer-reviewed empirical studies from 2012 to 2022 focused on this issue were included. The research identified multiple discrimination factors: cultural beliefs, inability to do heavy or fieldwork, sexual harassment, religion, low education levels, domestic conflict, mistrust, fear of competition, bureaucracy, withholding worker documents, disability, sexism, neoliberalism, virginity stigma, marital status, racial and ethnic differences, LGBT issues, egocentrism, feminism, workforce age, communication, lookism, and lack of community support. Culture was the leading factor (22% of studies), followed by perceptions of physical capability (10%), sexual harassment (8%), and educational barriers (8%). These findings show how Indonesian workplace discrimination results from the complex interplay of traditional gender norms, institutional structures, and economic pressures.